Food Metaphor in Jhumpa Lahiri's The Lowland - Retno Wulandari (MOZAIK HUMANIORA, 2017)
As food is now also observed through the lens of social sciences,  the relation of food and literature is inevitable. In diasporic identity, the existence of food as one of the elements that immigrants usually long for is thus unavoidable. This paper discusses the metaphor of food and foodways in the novel The Lowland by Jhumpa Lahiri. Through postcolonial analysis, the results show that food and foodways metaphorically represent nostalgia experienced by the main character. Food also becomes the field of showing identity, and negotiation process which bridges the binary cultural differences. Moreover, Lahiri also implies the metaphor of food as the oppression of women due to the existence of patriarchal values in the old world. Domesticity symbolized through food and foodways puts women in an uneasy situation. Lahiri also parallels the food as the medium of the old and new world: the poor and sufficiency, and the resistance to capitalism.Keywords : Food, nostalgia, identity, oppression, binary opposition